Mitochondrial ferritin is a functional iron-storage protein in cucumber (Cucumis sativus) roots - VIGANI, GIANPIERO; Tarantino, Delia; MURGIA, IRENE (Frontiers in Plant Science, 2013)
In plants, intracellular Fe trafficking must satisfy chloroplasts’ and mitochondrial demands for Fe without allowing its accumulation in the organelles in dangerous redox-active forms. Protein ferritin is involved in such homeostatic control, however its functional role in mitochondria, differently from its role in chloroplasts, is still matter of debate. To test ferritin functionality as a 24-mer Fe-storage complex in mitochondria, cucumber seedlings were grown under different conditions of Fe supply (excess, control, deficiency) and mitochondria were purified from the roots. A ferritin monomer of around 25 KDa was detected by SDS-PAGE in Fe-excess root mitochondria, corresponding to the annotated Csa5M215130/XP_004163524 protein: such a monomer is barely detectable in the control mitochondria and not at all in the Fe-deficient ones. Correspondingly, the ferritin 24-mer complex is abundant in root mitochondria from Fe-excess plants and it stores Fe as Fe(III): such a complex is also detectable, though to a much smaller extent, in control mitochondria, but not in Fe-deficient ones. Cucumber ferritin Csa5M215130/XP_004163524 is therefore a functional Fe(III)-store in root mitochondria and its abundance is dependent on the Fe nutritional status of the plant.